2018
DOI: 10.1016/j.bar.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance management systems' stability: Unfolding the human factor – A case from the Italian public sector

Abstract: The aim of this study is to examine the institutional context during the emergence of New Public Management (NPM), which created pressure on public sector organizations to implement performance management systems (PMSs), such as the balanced scorecard (BSC). Drawing on Granlund's framework ( 2001) and Giddens' (1979) structuration theory, we engage insights from a longitudinal case study of an Italian local authority to show how managers exercise agency before the mandated implementation of the BSC. This analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 78 publications
1
46
0
5
Order By: Relevance
“…Evidently, BSC and its implementation in the service sector is an uprising area of interest. For example, researchers have recognized the recent adoption of BSC by the public sector and studied it as a part of change management that is driving new public management ( Maran et al, 2018 ; Woods and Grubnic, 2008 ). A similar development has also been noticed in hospitality literature ( Phillips, 2007 ), where BSC when supplemented with change management can allow its successful implementation.…”
Section: A Roadmap For Future Researchmentioning
confidence: 99%
“…Evidently, BSC and its implementation in the service sector is an uprising area of interest. For example, researchers have recognized the recent adoption of BSC by the public sector and studied it as a part of change management that is driving new public management ( Maran et al, 2018 ; Woods and Grubnic, 2008 ). A similar development has also been noticed in hospitality literature ( Phillips, 2007 ), where BSC when supplemented with change management can allow its successful implementation.…”
Section: A Roadmap For Future Researchmentioning
confidence: 99%
“…PMM systems have undergone extensive advancement in public sector organisations and are used as a means of reinventing the government to be more efficient and effective (Hood, 1995). However, findings from various empirical studies have shown that PMM, with its rational system of managing performance, is problematic in the context of public organisations, in which resources are allocated based on political considerations and sphere of influence (Maran et al , 2018) and due to the presence of various stakeholders with competing interests (Mättö et al , 2020). Consequently, research evidence has shown that the PMM system is adopted to comply with legislation, but not substantively practice, as the systems in place are not aligned with values/organisational practices (McAdam et al , 2011; Rautiainen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, because of its implications for the way resources are allocated and the management of human resources, PMM entails a radical change in public sector organisations in developing countries characterised by different socio-economic and political contexts, and differing cultural norms and values (Marwata and Alam, 2006; Sutheewasinnon et al , 2016). Substantive PMM implementation requires the purposeful action of public officers in disrupting and changing existing practice, and in so doing, they need to influence the attitudes and reactions of different internal actors in terms of their acceptance of and engagement with the system (Dobija et al , 2019; Maran et al , 2018). Hence, the research question addressed in this paper is: what types of work are undertaken by the public managers of local government in a developing country to institutionalise a PMM system that is mandated by the central government?…”
Section: Introductionmentioning
confidence: 99%
“…Considering what is said, the strategic HRM and employee performance management in the public sector needs to maintain a coherent and effective approach. Seeking to apply appropriate private sector models in the public sector, the new public management introduces the balanced scorecard model (Maran, Bracci, & Inglis, 2018). Although this model was first introduced for the private sector, Kaplan and Norton (2001a) presented a modified version of it for the public sector.…”
Section: Literature Reviewmentioning
confidence: 99%